The consequences of flexible work for health: are we looking at the right place? : Association between working conditions and health - Benach, Joan (2002)
Fil: Benach, Joan. Universitat Pompeu Fabra. Department of Experimental and Health Sciences. Center for Research in Occupational Health; España